Peran Sekolah Lansia Selaras Dalam Meningkatkan Kesejahteraan Lanjut Usia di Desa Tandam Hulu II Kabupaten Deli Serdang - Wildah Veizy Jasmin; Hodriani Hodriani (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2025)
ABSTRACTThis research aims so understand the role of the Selaras Elderly School in improving the welfare of elderly inTandam Hulu II village, Deli Serdang Regency. It examines how the Selaras Elderly School realize independent, active, productive and dignified elderly individualsacross seven dimensions of resilient elderly. This study employs a qualitative research method with a descriptive approach. The sujects of this research include the Head of Tandam Hulu II village, the Chairperson of the Selaras Elderly School, BKL cadres from Tandam Hulu II Village, Student of the Selaras Elderly School, families of the student. And representative from BKKBN of North Sumatera Provincial Government. The types of data used in this study are primary and secondary data. Primary data were obtained though observation, interviews, and documentation. Meanwhile, secondary data were gathered from books, journals, articles, and website related to the research topic. The data analysis techniques employed include data reduction, data presentation, and conclusion drawing. The results indicate that the Selaras Elderly School is an appropriateeducational institution for empowering the elderly to become resilientand prosperous. In enchancing elderly welfare, the Selaras Elderly School provides services based on seven dimensions relevant to elderly care in every avtivity: spiritual dimension, phyisical dimension, emotional dimension, intellectual dimension, social community dimension, vocational dimension, and environmental dimension.Key Word : Elderly, Elderly School, Elderly Welfare ABSTRAKPenelitian ini bertujuan untuk mengetahui Peran Sekolah Lansia Selaras dalam Meningkatkan Kesejahteraan Lansia di Desa Tandam Hulu II Kabupaten Deli Serdang. Bagaimana Sekolah Lansia Selaras mewujudkan lansia yang mandiri, aktif, dan produktif, serta bermartabat dalam tujuh dimensi lansia tangguh. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif. Subjek penelitian yaitu kepala desa Tandam Hulu II, siswa Sekolah Lansia Selaras, keluarga siswa lansia selaras, dan perwakilan dari BKKBN Pemerintah Provinsi Sumatera Utara. Jenis data yang digunakan dalam penelitian ini adalah dara primer dan data sekunder. Data primer diperoleh dari oservasi, wawancara, dan dokumentasi. Sedangkan data sekunder didapat melalui buku, jurnal, dan artikel serta website yang berkaitan dengan topik penelitian. Teknik analisis data yang dipakai meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa sekolah lansia selaras merupakan lembaga pendidikan yang tepat untuk dijadikan sebagai tempat pemerdayaan lansia yang tangguh dan sejahtera. Dalam meningkatkan kesejahteraan lansia, Sekolah Lansia Selaras Melaksanakan pelayanan berdasarkan tujuh dimensi lansia pada setiap kegiatannya, yaitu dimensi spiritual, dimensi fisik, dimensi emosional, dimensi intelektual, dimensi sosial kemasyarakatan, dimensi vokasional, dan dimensi lingkungan.Kata Kunci: Lansia, sekolah lansia, kesejahteraan lansia